Immunomodulatory Role of Ocimum gratissimum and Ascorbic Acid against Nicotine-Induced Murine Peritoneal Macrophages In Vitro. (18th December 2011) - Mahapatra, Santanu Kar; Chakraborty, Subhankari Prasad; Roy, Somenath
Abstract : The aim of this present study was to evaluate the immune functions and immune responses in nicotine-induced (10 mM) macrophages and concurrently establish the immunomodulatory role of aqueous extract of Ocimum gratissimum (Ae-Og) and ascorbic acid. In this study, nitrite generations and some phenotype functions by macrophages were studied. Beside that, release of Th1 cytokines (TNF- α, IL-12) and Th2 cytokines (IL-10, TGF- β ) was measured by ELISA, and the expression of these cytokines at mRNA level was analyzed by real-time PCR. Ae-Og, at a dose of 10  μ g/mL, significantly reduced the nicotine-induced NO generation and iNOSII expression. Similar kinds of response were observed with supplementation of ascorbic acid (0.01 mM). The administration of Ae-Og and ascorbic acid increased the decreased adherence, chemotaxis, phagocytosis, and intracellular killing of bacteria in nicotine-treated macrophages. Ae-Og and ascorbic acid were found to protect the murine peritoneal macrophages through downregulation of Th1 cytokines in nicotine-treated macrophages with concurrent activation of Th2 responses. These findings strongly enhanced our understanding of the molecular mechanism leading to nicotine-induced suppression of immune functions and provide additional rationale for application of anti-inflammatory therapeutic approaches by O. gratissimum and ascorbic acid for different inflammatory disease prevention and treatment during nicotine toxicity.